Comparison of biotinylated monoclonal and polyclonal antibodies in an evaluation of a direct rapid immunohistochemical test for the routine diagnosis of rabies in southern Africa - Nel, Louis Hendrik (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 2013.